Determining the Phosphorus Release Curve for Sunphase HT Phytase from 250 to 2,000 FTU/kg in Nursery Pig Diets - Ty H. Kim; Katelyn N. Gaffield; Mike D. Tokach; Joel M. DeRouchey; Jason C. Woodworth; Robert D. Goodband; Jordan T. Gebhardt; Ying Zhou; Xuerong Song; Xiuyi Wu; Mikhail Y. Golovko; Svetlana A. Golovko (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 280 pigs (DNA 241 × 600; initially 22.9 ± 0.52 lb BW) were used in a 21-d growth study to determine the available P (aP) release curve for Sunphase HT phytase (Wuhan Sunhy Biology Co., Ltd.; Wuhan, P.R. China). At approximately 19 d of age, pigs were weaned, randomly allotted to pens, and fed common starter diets. Pigs were blocked by average pen body weight (BW) and randomly allotted to 1 of 7 dietary treatments on d 21 post-weaning, considered d 0 of the study. Dietary treatments were derived from a single basal diet, and ingredients including phytase, monocalcium P, limestone, and sand were added to create the treatment diets. Treatments included 3 diets containing increasing (0.11, 0.19, and 0.27% aP) inorganic P from monocalcium P, or 4 diets with increasing phytase (250, 500, 1,000, or 2,000 FTU/kg) added to the diet containing 0.11% aP. All diets were corn-soybean meal-canola meal-based and were formulated to contain 1.24% SID Lys and an analyzed Ca:P ratio of 1.10:1. Prior to the beginning of the study, all pigs were fed a diet containing 0.11% aP for a 3-d period (d 18 to 21 post-weaning). At the conclusion of the study, 1 pig, closest to the mean weight of each pen, was euthanized and the right fibula, rib, and metacarpal were collected to determine bone ash and density. For the overall experimental period, pigs fed increasing levels of aP from inorganic P had improved (linear,P≤ 0.014) ADG, F/G, and final BW. Similarly, pigs fed increasing phytase had increased (linear,P≤ 0.011) ADG and final BW as well as improved (quadratic,P= 0.017) F/G. For fibula bone ash weight and percentage bone ash, rib bone ash weight and bone density, and all metacarpal bone properties, pigs fed increasing levels of aP from inorganic P exhibited a linear improvement (P≤ 0.019), with a quadratic response (P≤ 0.030) for fibula bone density and rib percentage bone ash. Additionally, pigs fed increasing phytase had increased (P<0.05) bone ash weight, percentage bone ash, and bone density in either a linear or quadratic fashion depending on the bone analyzed. The available P release curve generated for Sunphase HT for percentage bone ash combining values from right fibula, rib, and metacarpal is: aP = (0.360 × FTU) ÷ (2,330.250 + FTU).
Keywords: bone ash; growth; nursery pigs; phosphorus release; phytase; plasma inositol